The Development of Antonym Knowledge in American Sign Language (ASL) and Its Relationship to Reading Comprehension in English. Issue 4 (December 2014) - Novogrodsky, Rama; Caldwell‐Harris, Catherine; Fish, Sarah; Hoffmeister, Robert J.
<x xml:space="preserve">Abstract</x> It is unknown if the developmental path of antonym knowledge in deaf children increases continuously with age and correlates with reading comprehension, as it does in hearing children. In the current study we tested 564 students aged 4–18 on a receptive multiple‐choice American Sign Language (ASL) antonym test. A subgroup of 138 students aged 7–18 took the Stanford Achievement Test reading comprehension test. The results showed that antonym knowledge depended more strongly on age for deaf children with deaf parents than for deaf children with hearing parents. This indicates more developmentally typical acquisition for deaf children with deaf parents, consistent with early natural language exposure. Multiple regressions demonstrated that ASL antonym knowledge eliminated the advantage of deaf parents for reading. This establishes a language effect of ASL on reading comprehension in English.